Effects of customer cooperation on knowledge generation activities and innovation results of firms - Gloria Sánchez-González; Liliana Herrera (BRQ Business Research Quarterly, 2014)
This study has analyzed the effect of cooperation with customers on firms' innovation activities. This issue is particularly novel and important as customers provide information that will be very useful to generate new products and to make the innovation process more efficient. This paper makes important contributions to the literature by analyzing how the cooperation with customers affected the creation of technological knowledge and the economic returns derived from such knowledge. Results have shown that firms cooperating with customers increased investments geared toward expanding the technological knowledge base within the firm's technological domain yet managed to reduce investments oriented to extend the frontier of technological knowledge, at least in the short term. It was also observed, that this cooperation had positive effects on firms' economic returns derived from the sales of products new for the market allowing companies to maintain a competitive advantage over their rivals."
Keywords: 650; Customer cooperation; Basic research; Applied research; Technological development; Innovation result